Islamism Denounced: Madura Kiais’ Perspective of Nationalism - A'la, Abd; Muktafi, Muktafi; Bakar, Abu; Zamzami, Mukhammad; Aniq, Ahmad Fathan (Universitas Islam Negeri Madura, 2021)
The transmission of Islamism among the kiais and their students in Madura has become more critical to examine in the last decade. However, some kiais of Nahdlatul Ulama (NU) in Bangkalan Madura see that Islamism or political Islam will gradually erode their national commitment. This article intends to reinterpret the nationalism vision of several kiais of NU and measure the extent of their views on the ideology of Islamism discoursed by the Islamic Defenders Front (FPI). By interviewing several kiais, this study finds that the propagation of Islamism in Bangkalan has not been as massive as occurred in Pamekasan, another sub-districts in Madura. The FPI-style Islamism in Bangkalan has been propagated only by a small group though they are vigorously active on social media. The majority of the NU community remains devoted to nationalism, committing that the NKRI is the final state. Islamic moderation promulgated by the kiais has been widely accepted and deeply rooted among the NU community. They believe nationalism and religion should not be separated from the spirit of their struggle (khittah). These two elements have united within their fighting spirit and become the primary trigger in devoting themselves to the nation and state to preserve national sovereignty and the integrity of Indonesia.